Compton Bassett and Yatesbury, North Wiltshire: Settlement Morphology and Locational Change - Andrew Reynolds (Papers from the Institute of Archaeology, 1994)
This paper is concerned with aspects of the results of excavation and survey undertaken on behalf of the Compton Bassett Area Research Project (CBARP) since 1991. Evidence pertaining to the study of the Anglo-Saxon and medieval landscape is the primary consideration, although earlier evidence is also taken into account Far from being a detailed statement, it is the intention here to give only a brief account of the perceived evolution of Compton Bassett and Yatesbury. Additionally, certain approaches to the interpretation of rural settlements are questioned.
Keywords: rural; settlement